2019
DOI: 10.1155/2019/5087847
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 Function in the Skin and Isolated Keratinocytes Is Modulated by Hyperglycemia

Abstract: Diabetes currently affects over twenty-five million Americans. Annual health care cost of diabetes exceeds $254 billion and is associated with a distinct set of diabetic complications that include delayed wound healing and diabetic ulcers. Interleukin 6 (IL-6) plays an important role in wound healing and is known to be elevated in the serum of both type I and type II diabetes patients. This study assesses the expression and function of IL-6 in the hyperglycemic epidermis and keratinocyte culture. Streptozotoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
3
20
0
1
Order By: Relevance
“…As the primary cell type in the epidermis, keratinocytes produce large amounts of cytokines to initiate and regulate inflammation, including IL-1, -6, -7, -8, -10, -12, -15, -18, and -20, and TNF-α [ 158 ]. Although elevated IL-8 [ 159 ], IL-1 α [ 160 ], TNF-α [ 161 ], IL6 [ 19 , 162 ], and CCL2 [ 163 ] levels have been observed in human chronic wounds, these cytokines are not specifically produced by keratinocytes. Indeed, few studies have provided clear evidence of the contribution of keratinocytes-derived cytokines to wound healing or chronic wound pathology.…”
Section: Impaired Immune Functions Of Keratinocytes In Chronic Nonmentioning
confidence: 99%
“…As the primary cell type in the epidermis, keratinocytes produce large amounts of cytokines to initiate and regulate inflammation, including IL-1, -6, -7, -8, -10, -12, -15, -18, and -20, and TNF-α [ 158 ]. Although elevated IL-8 [ 159 ], IL-1 α [ 160 ], TNF-α [ 161 ], IL6 [ 19 , 162 ], and CCL2 [ 163 ] levels have been observed in human chronic wounds, these cytokines are not specifically produced by keratinocytes. Indeed, few studies have provided clear evidence of the contribution of keratinocytes-derived cytokines to wound healing or chronic wound pathology.…”
Section: Impaired Immune Functions Of Keratinocytes In Chronic Nonmentioning
confidence: 99%
“…Studies carried out in genetically modified animal models imply that IL‐6 has a profound role in both innate and adaptive immunity to protect the host from a variety of infections, mainly against the bacterial and fungal pathogens (Rose‐John et al., 2017). IL‐6 is an important cytokine implicated in wound healing (Lee et al., 2019), and according to Gerstein et al. (1993), many scientific reports have proved age‐related differences in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in genetically modified animal models imply that IL-6 has a profound role in both innate and adaptive immunity to protect the host from a variety of infections, mainly against the bacterial and fungal pathogens (Rose-John et al, 2017). IL-6 is an important cytokine implicated in wound healing (Lee et al, 2019), and according to Gerstein et al (1993) wounds with the inflammation, we suppose that the altered levels of IL-6 observed during aging in our study may be partially responsible for the delayed wound healing commonly observed in the elderly. Several previous studies have shown a rise in blood circulatory IL-6 during aging (Forsey et al, 2003;Stowe et al, 2009), however, Nevalainen et al (2015) demonstrate a low baseline expression level of the IL-6 transcript in aged PBMCs.…”
Section: F I G U R Ementioning
confidence: 99%
“…Experimental research conducted by Lin et al [ 10 ] explains that in rats with IL-6 deficiency there is a decrease in the number of angiogenic and fibrogenic growth factors so that angiogenesis and collagen deposition are delayed. The study by Lee et al [ 14 ] explains IL-6-deficient mice showed an early phase delay in wound healing, as well as in hyperglycemic mice. IL-6 was significantly higher (sixfold) in hyperglycemic animals at days 1, 7, and 10 [ 14 ].…”
Section: Main Textmentioning
confidence: 99%
“…The study by Lee et al [ 14 ] explains IL-6-deficient mice showed an early phase delay in wound healing, as well as in hyperglycemic mice. IL-6 was significantly higher (sixfold) in hyperglycemic animals at days 1, 7, and 10 [ 14 ]. Our study shows an almost significant change in IL-6 expression in the small stitch group between days 4 and 7.…”
Section: Main Textmentioning
confidence: 99%